A comparison of kinematics between overarm throwing with 20% underweight, regular, and 20% overweight balls - van den Tillaar, R.; Ettema, G. (Journal of Applied Biomechanics, 2011)
The aim of this study was to compare the kinematics in throwing with a regular weighted handball with 20% lighter and heavier balls in female experienced handball players. In total, eight joint movements during the throw were analyzed. The analysis consisted of maximal angles, angles at ball release, and maximal angular velocities of the joint movements and their timings during the throw. Results on 24 experienced female team handball players (mean age 18.2 ± 2.1 years) showed that the difference in ball weight affected the maximal ball velocity. The difference in ball release velocity was probably a result of the significant differences in kinematics of the major contributors to overarm throwing: elbow extension and internal rotation of the shoulder. These were altered when changing the ball weight, which resulted in differences in ball release velocity.